The relationship between steroid treatment and mortality in patients with COVID-19 followed up in an intensive care unit - Huseyin Ali Ozturk; Fatih Necip Arici (PeerJ)
Aim Optimal treatment of the coronavirus disease (COVID-19) is still unclear. It has been reported that the use of different doses of corticosteroid treatments may reduce mortality. In our study, we aimed to find the effect of corticosteroid treatment dose on mortality of patients followed up in intensive care due to COVID-19. Methods Our retrospective, descriptive and single-centre study included 102 patients diagnosed with COVID-19 who were followed up in intensive care unit, 28 of whom received pulse steroids and 74 of whom received high dose steroids. Laboratory values, duration of intensive care unit and mortality rates of the patients were evaluated. Results Mortality was found to be statistically significantly lower in the group receiving pulse steroid compared to the group receiving high dose steroid. In multivariate logistic regression analysis, age and pulse steroid were found to be independent predictors of mortality. According to this analysis, each 10-year increase in age increased mortality by 4.8%, whereas pulse steroid decreased mortality by 79.4%. Conclusion In our study, we found that mortality was statistically significantly lower in the group of patients receiving pulse steroids than in the group receiving high dose steroids. We found that the number of patients using pulse steroids was statistically significantly lower in the group with mortality. We found that age and pulse steroid independently determined the patients with mortality.